High resolution magnetic parameters and correlative model age of the 26 meter Suhia Kladenetz loess-palesol seqeunce near the city of Pleven in Bulgaria - Diana Jordanova; Christian Laag; Neli Jordanova; France Lagroix; Bozhurka Georgieva; Daniel Ishlyamski; Yohan Guyodo (PANGAEA, 2022)
The Suhia Kladenetz loess-paleosol sequence was sampled in 2018 on freshly cleaned vertical faces segmenting the larger quarry steps in two to three sub-sections. A continuous column of sediment was prepared and sampled at a 2 cm depth resolution. Slices of bulk sediment of about 10 x 6 x 2 cm in dimension (approx. 300g of material) were taken per sampling interval. The SK sequence is 26.72 m in total vertical thickness, which at a 2 cm continuous depth sampling resolution results in 1336 bulk sediment samples collected. Laboratory measurements of magnetic susceptibility, frequency dependence of magnetic susceptibility both absolute values and percentage, anhysteretic remanent magnetisation, isothermal remanent magnetisation, coercivity and coercive force are reported. Data of two correlative age models built from (1) the correlation of the frequency dependent magnetic susceptibility to the LR04 benthic foraminifera oxygen isotope record, and (2) the correlation of the ratio of a 2T isothermal remanent magnetisation and magnetic susceptibility to the EPICA Dome C (EDC) dust flux record. Estimates of sedimentation rates based on the correlative ages models are also reported.